Piezoelectric energy harvesting interface with fast open-circuit voltage sampling - Kim, Hyeon-Joong; Yu, Chong-Gun (Journal of Asian Scientific Research, 2024)
This paper presents a piezoelectric energy harvesting interface with fast open-circuit voltage (VOC) sampling and a wide operating frequency range. The fractional open-circuit voltage (FOCV) method is the primary method for maximum power point tracking (MPPT) in energy harvesting systems, due to its easy implementation and relatively low cost. For this method to be efficient, it is necessary to shorten the time required for VOC sampling. To minimize power loss due to VOC sampling, a novel technique is proposed that is capable of sampling the VOC within a time shorter than half a cycle by using an adaptive tracking pulse instead of conventional fixed ones. We also present a peak detector design technique that can operate across a broad frequency spectrum and adapt to diverse vibration scenarios. The proposed technique reduces the duty cycle of the tracking pulse to 0.42%, which is 3.7 times smaller than the conventional 1.56%. The proposed circuit, designed using a 0.35μm complementary metal oxide semiconductor (CMOS) process, consumes just 94nA at 100Hz, 3V VOC, and a 1kΩ load. In a 2 4V VOC range and a 15 500Hz frequency range, the MPPT efficiency exceeds 95%, peaking at 99.9%, and the power efficiency remains over 93%, reaching a maximum of 97.7%.